Energy Optimized YOLO: Quantized Inference for Real-Time Edge AI Object Detection - Chiam, Hwee Min; Wong, Yan Chiew; Sarban Singh, Ranjit Singh; Anand, T. Joseph Sahaya (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2025)
Efficient real-time object detection is a critical requirement in edge computing applications, such as smart surveillance, where resource constraints pose significant challenges. Existing deep learning methods often struggle to balance accuracy and efficiency, particularly when deployed on hardware with limited computational resources. This work focuses on developing a quantized object detection system utilizing advanced deep learning models to improve inference performance on edge devices, Zedboard and Jetson Nano. The Zedboard, an FPGA platform without GPU acceleration, executes a quantized YOLOv3-tiny model with ultra-low power consumption of 2.2W but requires over 3 seconds per inference, making it unsuitable for real-time applications. In contrast, the Jetson Nano, running an optimized YOLOv7-tiny model with FP16 quantization and GPU acceleration, achieves a processing speed of 38 FPS with mAP of 46.3%, while maintaining a low power consumption of 5.1W. Based on the results, this work presents a practical solution for real-time object detection in resource-constrained environments by demonstrating the benefits of combining quantized deep learning models with GPU acceleration. Future work could focus on fine-tuning models for specific applications, such as traffic monitoring, to improve the detection of vehicles, pedestrians, and traffic signs in dynamic environments.